TOURISM IN BAKA STUPAS AND SURROUNDING WITH HAHSLM PERSPECTIVE - RM Aziz (Badan Pelaksana Rinjani-geopark Rinjani Lombok, 2021)
Tourism activity is a sector that plays an important role in regional development and development efforts by contributing to the income of an area. One of the areas that has developed due to the contribution of the tourism sector is Magelang Regency, Central Java. The existence of the tourist area of Borobudur Temple which has an international scale contributes greatly to the income of the people around it. 72 Borobudur stupas which are a reflexivity of the interference quantum physics pattern based on the Hahslm constant 472319 approach in the Covid-19 economic era. Modern physics is phenomenal in quantum reality with its wave interfer-ence. Similarity is found in the meaning of 7 waves and 2 gaps in the interference physics process, then reflected in the code of the 72 stupas that were built. The conclusion of the research is that 72 Borobudur stupas are a reflection of the interference part of the Hahslm 472319 constant in the Covid-19 economic era. The method used is the Hahslm 472319 equation which refers to QS. Al-Hijr [15]: 87. The result obtained is that the largest historical temple building in the world, namely Borobudur has 72 stupas, refer-ring to phenomenal events with absolute and differentiation.